Answer:
1)
![((P -3b))/(3) = a](https://img.qammunity.org/2023/formulas/mathematics/high-school/jug6w90cuooqkj8c1qb2zx2s3tx2lbbrvr.png)
2)
![((v-u))/(a) =t](https://img.qammunity.org/2023/formulas/mathematics/high-school/rzkkjl5mrzawum9mziz5pkybj1x87drzik.png)
3)
![x = (( -12-6y))/(5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipgn4nhn9cjqkm6vdngapucxjjoapahe10.png)
4)
![((A-9))/(3) =b](https://img.qammunity.org/2023/formulas/mathematics/high-school/rxwk2vz1mq4koscykgsxduo2afwy4ur3ok.png)
5)
![(5(y+12))/(2) =x](https://img.qammunity.org/2023/formulas/mathematics/high-school/sfti0codrzwo4kdwhlwt3qykfyr94b5ieq.png)
Explanation:
1) P = 3a + 3b
First, take 3b to the left side.
P - 3b = 3a
Divide both sides by 3.
![((P -3b))/(3) = a](https://img.qammunity.org/2023/formulas/mathematics/high-school/jug6w90cuooqkj8c1qb2zx2s3tx2lbbrvr.png)
2) v = u + at
First, take u to the left side.
v - u = at
Divide both sides by a.
![((v-u))/(a) =t](https://img.qammunity.org/2023/formulas/mathematics/high-school/rzkkjl5mrzawum9mziz5pkybj1x87drzik.png)
3) 5x + 6y + 12 = 0
First, take 12 to the right side.
5x + 6y = -12
Take 6y to the right side.
5x = -12 - 6y
Divide both sides by 5.
![x = (( -12-6y))/(5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipgn4nhn9cjqkm6vdngapucxjjoapahe10.png)
4) A = 3b + 9
First, take 9 to the left side.
A - 9 = 3b
Divide both sides by 3.
![((A-9))/(3) =b](https://img.qammunity.org/2023/formulas/mathematics/high-school/rxwk2vz1mq4koscykgsxduo2afwy4ur3ok.png)
5) y = 2/5x – 12
First, take -12 left side.
y + 12 = 2 / 5x
Multiply both sides by 5.
5 ( y + 12 ) = 2x
Divide both sides by 2.
![(5(y+12))/(2) =x](https://img.qammunity.org/2023/formulas/mathematics/high-school/sfti0codrzwo4kdwhlwt3qykfyr94b5ieq.png)